Cellular Evidence of Exosomes in the Reproductive Tract of Chinese Soft‐Shelled Turtle Pelodiscus sinensis. Issue 1 (20th February 2017) - Waqas, Muhammad Yasir; Zhang, Qian; Ahmed, Nisar; Yang, Ping; Xing, Guipei; Akhtar, Masood; Basit, Abdul; Liu, Tengfei; Hong, Chen; Arshad, Muhammad; Rahman, Hafiz Muhammad Saif‐Ur; Chen, Qiusheng
GRAPHICAL ABSTRACT: The present study focuses on the characterization of the ultrastructure in the oviduct of Chinese soft‐shelled turtle. Second, this is a novel study focusing on the identification of exosomes in reptile species. Localization of antibody in different months shows that the exosomes shedding from the epithelial cells are more in sperm storage period as compared to breeding period. Transmission electromicrographs give the novel evidence about the existence of exosomes in this species ABSTRACT: The oviduct is a location of egg production, fertilization, and sperm storage. While its secretions have broadly attributes toward different physiological functions. We examined the ultrastructure of oviduct epithelium and glands in relation to the secretions, particularly with exosomes origin in Chinese soft‐shelled turtle Pelodiscus sinensis using immunohistochemistry and transmission electron microscopy. The ciliated epithelial and gland cells were involved in the release of exosomes and secretions into lumen throughout the year. The exosomes were either released directly from epithelium or in relation with multivesicular body (MVB). The average size of the particles varies between 50 and 130 nm. These exosomes were also widely distributed in the epithelial ciliated cells and pericytoplasm of glands lumen. Intracellular MVB was characterized by membrane‐bounded exosomes of different sizes. Exosomes were also found in close contact with the cilia and sperm membrane in the lumen, which is suggestive of their fusogenic properties. Immunohistochemistry results showed strong to moderate positive expression of exosomes, in ciliated and gland cells, during January, September, and December, as it is the time of sperm storage in this turtle, whereas they showed moderate to weak level of expression during breeding season (May). This is first study about identification of the exosomes in female turtles. Epithelial and glandular exosomes, intracellular MVB, secretions, and secretory vesicles give this turtle specie a unique secretory morphology and a potential model for investigating the secretory nature of the oviduct.